Strengthening Furudul Ainiyah Based On Excellency In Pesantren; Assure Approach - Abdullah; Sultani; Hasan Baharun; Izzur Rizqiyah (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2023)
This study aims to analyze the strengthening of excellence-based furudhul ainiyah through the ASSURE approach to make learning effective at the Nurul Jadid Islamic boarding school. Research subjects use a qualitative approach to the type of case study. Research data was obtained from observations, interviews, and documentation. The data analysis was carried out in stages, starting with presenting, reducing, and drawing conclusions. The study results show that the ASSURE approach used by teachers in teaching furudul ainiyah material can create effective, efficient, and meaningful learning conditions. This is because the teacher pays attention to and follows the learning design that has been outlined. This research provides implications about the importance of learning design that must be carried out by all teachers to realize learning objectives optimally.